Seasonal Influence on Sexual Behaviour of Jaffrabadi Buffalo Bulls - Parmar, KH; Dhami, AJ; Kavani, FS; Solanki, GB; Murthy, KS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was carried out on four mature Jaffrabadi breeding bulls (4–6 years old) maintained at Cattle Breeding Farm, JAU, Junagadh for a period of 8 months during winter and summer. The seasonal and bull variations in sexual behavior traits were studied. A total of 64 observations (32 per season, 8 per bull) were availed at the fortnightly interval. The mean values/ scores for temperament (0–5 scale), libido (0–9 scale), penile erection (0–4 scale), protrusion (0–4 scale), intensity of thrust (0–4 scale), reaction time (sec) and Flehmen reaction (0, 1) during winter season were 1.28 ± 0.08, 6.75 ± 0.19, 3.22 ± 0.74, 2.88 ± 0.59, 3.15 ± 0.65, 125.00 ± 6.92 and 0.91 ± 0.43, respectively, while the respective values in summer season were 2.22 ± 0.07, 5.93 ± 0.43, 2.84 ± 0.65, 2.75 ± 0.59, 2.93 ± 0.13, 143.5 ± 7.07 and 0.88 ± 0.06. There were significant differences among seasons for temperament, libido and penile erection score of Jaffrabadi bulls. Significant differences among bulls were also found for libido score, the intensity of thrust and reaction time in the winter season, and for ejaculatory thrust in the summer season. All these traits were highly significantly and positively interrelated (r = 0.353 to 0.512), except Flehmen reaction and reaction time which were negatively correlated with all other behavioral traits (r = –340 to –0.499). Summer in general significantly exerted an adverse effect on the sexual behavior of Jaffrabadi bulls, and winter was the favored season. It could be concluded from the study that the Jaffrabadi bulls had good sexual behavior scores throughout both the seasons, however, bulls showed better sexual behavior during winter as compared to summer.